Drug use beyond the licence in palliative care: A systematic review and narrative synthesis. (June 2019) - Hagemann, Vera; Bausewein, Claudia; Remi, Constanze
Background: Drug use beyond the licence (off-label use, off-label drug use) is a common practice in palliative care and respective recommendations can often be identified in the literature. It is both risky and offers opportunities at the same time and, therefore, requires special attention in clinical practice. Aim: To determine the prevalence of off-label drug use in palliative care and to identify, evaluate and critically appraise studies describing the clinical practice, healthcare professionals' awareness, knowledge and attitudes towards off-label-use and management strategies. Design: Systematic literature review following the guidance of the Centre for Reviews and Dissemination. Data sources: Medline, Embase, Web of Science and Current Contents Connect were searched in July 2018 as well as hand searches. The reference lists of pertinent studies were screened for further relevant publications, and citation tracking was performed. Results: Eight studies met the inclusion criteria. Due to the variety in study designs and settings, no meta-analysis or meaningful statistical analysis was possible and a narrative synthesis of the data was performed. Frequency of off-label drug use ranged from 14.5% to 35%. Up to 97% of palliative care units did not have any policy or guidance on handling off-label drug use. About 20% of prescribers never obtain consent in the context of off-label use. Conclusion: Off-label use is common in palliative care with up to one-third of prescriptions affected. Challenges are often related to obtaining informed consent. Little is known about the decision-making process. More information and guidance for the prescribers are needed to enable safe handling of drugs outside their licence in palliative care.